Historical memory: discussion about its methodological status - Myslivets, Nikolay L. (Journal of the Belarusian State University. Sociology, 2023)
Some theoretical and methodological aspects related to the sociological study of the phenomenon of historical memory are presented. The experience of studying memory as a socio-cultural phenomenon in the history of socio-philosophical and socio-political thought is described. Historical memory is considered as an object of interdisciplinary research and acts as a mechanism that ensures the continuity of the development of society, the transfer of cultural achievements from generation to generation, the consolidation of society as a whole. The reasons for the actualisation of the study of historical memory and the main scientific approaches to its study are substantiated. A number of topical tasks and research directions that have emerged in recent years in the field of sociological study of historical memory are indicated.
Keywords: the past; history; memory; historical memory; sociology; methodology and research methods